Developing a toolkit for patients with COPD or chronic heart failure and their informal caregivers to improve person-centredness in conversations with healthcare professionals: A Design Thinking approach. Issue 11 (November 2022) - van Harlingen, Annet Olde Wolsink –; van de Ven, Leontine Groen –; Hasselaar, Jeroen; Thalen, Jos; Jukema, Jan; Vissers, Kris; Uitdehaag, Madeleen
Abstract: Background: The perspective of patients and informal caregivers is often not expressed in conversations with healthcare professionals which can have a negative impact on quality of care and quality of life. Objective: Describe the development of a toolkit for patients with COPD or chronic heart failure and their informal caregivers enabling them to explore and express their perspective in conversations with healthcare professionals. Patient involvement: Patients, informal caregivers and healthcare professionals were involved in the design process from problem definition to solution development. Method: Design Thinking Approach using eight co-creation sessions and qualitative data-collection methods. Nineteen patients, ten informal caregivers and thirteen healthcare professionals participated in one or more co-creation sessions. Homogenous subgroups of participants were used in session 1, 2 and 4 and mixed groups were used in session 3, 5 and 6. Session 7 and 8 were used to test prototype toolkits. Results: Three challenges to expressing the personal perspective to healthcare professionals, four statements defining the desired situation for conversations, eleven design criteria for the toolkit and ten selection criteria for tools were identified. This information was used to develop a prototype toolkit. Discussion: Most patients and informal caregivers had moderate to high levels of education and all participating healthcare professionals were female with a majority of nurses and only three physicians. It is possible that this has influenced the design of the toolkit. Practical value: The toolkit can support patients and informal caregivers in exploring and expressing their perspective in conversations with healthcare professionals. Feasibility of the toolkit and implications for healthcare professionals will be examined in a pilot implementation study. Highlights: In conversations with healthcare professionals patients with COPD or chronic heart failure and their informal caregivers find it challenging to. Make themselves known as unique individuals. Be heard in their experience and expertise in living with the disease. Think and talk about the future. The involvement of patients, informal caregivers and healthcare professionals in every step of the design process from problem definition to solution development.